Radio-frequency spectroscopy of a linear array of Bose-Einstein condensates in a magnetic lattice - Surendran, Prince Kurumthodathu; Whitlock, Shannon (Physical review. A, Atomic, molecular, and optical physics, 2015)
We report site-resolved radio-frequency spectroscopy measurements of Bose-Einstein condensates of 87Rb atoms in about 100 sites of a one-dimensional (1D) 10-μm-period magnetic lattice produced by a grooved magnetic film plus bias fields. Site-to-site variations of the trap bottom, atom temperature, condensate fraction, and chemical potential indicate that the magnetic lattice is remarkably uniform, with variations in the trap bottoms of only ±0.4 mG. At the lowest trap frequencies (radial and axial frequencies of 1.5 kHz and 260 Hz, respectively), temperatures down to 0.16μK are achieved in the magnetic lattice, and at the smallest trap depths (50 kHz) condensate fractions up to 80% are observed. With increasing radial trap frequency (up to 20 kHz, or aspect ratio up to ∼80) large condensate fractions persist, and the highly elongated clouds approach the quasi-1D Bose gas regime. The temperature estimated from analysis of the spectra is found to increase by a factor of about 5, which may be due to suppression of rethermalizing collisions in the quasi-1D Bose gas. Measurements for different holding times in the lattice indicate a decay of the atom number with a half-life of about 0.9 s due to three-body losses and the appearance of a high-temperature (∼1.5 μK) component which is attributed to atoms that have acquired energy through collisions with energetic three-body decay products.
Gesehen am 25.06.2020